Penerapan Model Hybrid Convolutional Neural Network dan Long Short-Term Memory untuk Pengenalan Real-Time Sistem Isyarat Bahasa Indonesia (SIBI) - Hidayat, Syahrul; Via, Yisti Vita; Mandyartha, Eka Prakarsa (Universitas Budi Darma, 2024)
The Indonesian Sign Language System (SIBI) is an essential means of communication for the deaf and speech-impaired community in Indonesia. However, the limited public understanding of SIBI often hinders effective communication. This study develops a real-time SIBI sign recognition model to facilitate effective communication for the deaf and speech-impaired in Indonesia. The proposed method integrates a hybrid CNN-LSTM model to process the spatial and temporal information from the data. The study evaluates the model's performance on 25 types of SIBI signs. The dataset used consists of image sequences captured in real-time. Training is conducted with various parameters, including batch size, learning rate, and epochs. Model evaluation is carried out using accuracy, precision, recall, and f1-score metrics. The training and validation results show an increase in accuracy with the number of epochs: 87% at 10 epochs, 93% at 25 epochs, and 100% at 50 epochs. In real-time detection tests, the model with the image sequence dataset accurately detected SIBI signs in environments and with objects consistent with the dataset. The real-time detection program generates SIBI sign predictions in text form and sentences. The output of this research is efficient and accurate SIBI sign recognition technology. This research is expected to facilitate more effective communication for the deaf and speech-impaired community in Indonesia.